The Caspian Sea Encyclopedia - Zonn, Igor S. (Springer Berlin Heidelberg, 2010)
The Caspian Sea is a unique natural feature, the worlds largest landlocked water body. Historically the Caspian was one of the key zones where the interests of great powers such as Russia, Britain and Persia clashed. And the reason was and still is the oil the "black gold" of the Caspian and also the natural riches of the sea, its other gold the sturgeons with their black caviar. With this encyclopedia attempt to relate the Caspian story via an objective approach to the past and present of the sea where even today many geopolitical, economic, social and environmental issues are focused. These issues are vital not only to the Caspian countries, but other countries of the world as well. The encyclopedia contains about 1500 articles and terms providing descriptions of geographical features, cities, ports, transport routes, main oil and gas fields, aqueous biological resources, international treaties, national and international programs, research institutions, historical and archeological monuments, activities of prominent scientists, researchers, travelers, military commanders, oil industrialists and traders who had relation to the Caspian Sea. In addition this book gives the chronology of the most important events that became milestones in the history of the Caspian region development for more than 300 years, spanning a period from the times of Peter the Great till the present.